Access to Formal Credit of Indonesian SME : Study of SMEs in Sidoarjo - R.A. Sista Paramita; Tias A. Indarwati (Tirtayasa Ekonomika, 2020)
The aim of this study was to get a big picture of formal credit accessibility on Small Medium Enterprise (SME) in Sidoarjo. The sampling method used a purposive sampling, while the data was collected by distributing questionnaires (online and offline) from April 2nd - 30th 2018 from 100 respondent, who have access to credit at a formal financial institution. The study shows that the description of formal credit access in SMEs in Sidoarjo shows that it was classified as “easy”.  In general, applying for a credit at formal credit providers is quite easy for SMEs in Sidoarjo. But not all of SMEs have the same experience of accessing credit in an easy way, especially to increase the credit ceiling. There are still many SMEs were classified as a Microbusiness scale, which many SMEs still have a constraint that makes them cannot access credit easily. There is a large gap between SMEs that can access credit 1-2 times with SMEs that can access credit more than 10 times. This means that SMEs actually have access to formal credit, but not all SMEs have the same opportunity to access credit many times. The frequency of accessing credit is considered to be able to help business growth. This is in accordance with the existing facts, that at this time the availability of credit for microbusinesses has increased, such as KUR (People's Business Credit). This certainly can make it easier for SMEs to access credit.